An exploration of the factors which promote and impede correctional supervision effectiveness with regard to the juvenile or youth offenders - Van Zyl, Claudette (Rhodes University, Faculty of Humanities, Department of Social Work, 1999)
Youth Crime is increasing at an alarming rate and imprisonment as the only measure of punishment has become a contentious issue for the South African Correctional Services. National and international awareness has been raised about young people at risk in the 1992 campaign" Justice for the children: No child should be caged". In the words of Ruth Morris: " Prisons are not the greatest. They breed bitterness and crime, destroy people who work and live in them and its not nice to cage your fellow human beings. Prisons cost more than the best university education, while giving appalling results". (1993 (1) SA 476). The question that needs to be asked is whether imprisonment really does effect the punitive motives of deterrence, retribution, protecting the community and rehabilitation of the offender. The introduction of correctional supervision as a sentencing option has ushered in a new phase in our criminal justice system. The South African Model of correctional supervision is described as a community-based sentence that is served within the community and the probationer is subject to stringent conditions such as house arrest, community service, monitoring and the attendance of treatment programmes. The study aimed to: * identify the variables that appear to be operating in determining the successful and or unsuccessful correctional supervision sentences with young offenders; (the terms effectiveness and successful are used interchangeably). * contribute to a better understanding of working with young offenders in the community and to make positive recommendations concerning their rehabilitation. The design applied in this study was the exploratory-descriptive design. It was exploratory since the field of correctional supervision at this stage is not well developed and descriptive because the researcher described features of this phenomenon. This was combined with an empirical investigation that explored the youths experience on correctional supervision. Another component of the empirical investigation consisted of how the parents or significant other as well as the supervision committee perceived the respondents adjustment on correctional supervision. The findings of the empirical investigation clearly showed that although the respondents found house arrest extremely difficult to comply with, their overall functioning and adjustment in the community was positive. Factors that emerged from the study that can promote a successful correctional supervision sentence were factors such as positive support systems that can instill discipline, no involvement in gangsterism, no family pathologies such as alcoholism, family violence and financial problems. Factors such as negative attitude of staff members, familial problems, stringent house arrest conditions, financial problems impeded the youths functioning on correctional supervision. The correctional social worker together with the multi-disciplinary team both have a cardinal role to play in the treatment of the young offender. The various professions with their expertise have a major role to play in the treatment programmes geared to assist the young offender to reintegrate and function positively in the community
Keywords: Juvenile corrections; Juvenile delinquency; Juvenile delinquents; Social work with juvenile delinquents